2012
DOI: 10.1021/ja312125a
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Modularity of Ion-Paired Chiral Ligands for Palladium-Catalyzed Enantioselective Allylation of Benzofuran-2(3H)-ones

Abstract: A highly enantioselective allylation of benzofuran-2(3H)-ones is achieved under Pd catalysis by taking full advantage of the structural modularity of ion-paired chiral ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(33 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…Starting from optically pure (R)‐BINOL 7 , the hydroxyl was protected by methyl groups, which could afford desired product 8 in high yield. Iodization led to the 3,3′‐diiodinated derivative 9 . Subsequently, Ni‐catalyzed Kumada‐type and Palladium‐catalyzed Suzuki coupling obtained the corresponding 3,3′‐neopentyl intermediate 10c and 3,3′‐ n Octyl intermediate 10d , respectively, which were used directly in the next step without further purification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from optically pure (R)‐BINOL 7 , the hydroxyl was protected by methyl groups, which could afford desired product 8 in high yield. Iodization led to the 3,3′‐diiodinated derivative 9 . Subsequently, Ni‐catalyzed Kumada‐type and Palladium‐catalyzed Suzuki coupling obtained the corresponding 3,3′‐neopentyl intermediate 10c and 3,3′‐ n Octyl intermediate 10d , respectively, which were used directly in the next step without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…Iodization led to the 3,3′‐diiodinated derivative 9 . Subsequently, Ni‐catalyzed Kumada‐type and Palladium‐catalyzed Suzuki coupling obtained the corresponding 3,3′‐neopentyl intermediate 10c and 3,3′‐ n Octyl intermediate 10d , respectively, which were used directly in the next step without further purification. Different metal catalysts have been screened, and we found that Ni (PPh 3 ) 2 Cl 2 was suitable for Kumada cross‐coupling, and Pd (dppf)Cl 2 was compliant with the Suzuki coupling.…”
Section: Resultsmentioning
confidence: 99%
“…Allyl bromide, allylboronic acid pinacol ester, and diethyl allylphosphonate exhibited very poor reactivity ( Table 1, entries 1-3), while allyl acetate and carbonates showed good reactivity to yield the desired product. [14] Next, the cross-coupling reaction of 1a with allyl ethyl carbonate (2a) was employed as the model reaction to optimize the reaction conditions [Eq. [13] Allyl ethyl carbonate behaved as the most effective allylating reagent to form 3a in 81% yield (Table 1, entries 4-8).…”
mentioning
confidence: 99%
“…In recent years, the successful employments of chiral phosphate metal salts were found to be effective in catalyzing enantioselective transformations. [8,9] At the same time, it is well known that cinchona scaffolds combined with a wide range of metal ions have also led to the development of new stereocontrolled reactions. [10] In light of these achievements, we envisioned that the combination of these two types of privileged chiral scaffolds together linking by a metal center, could serve as a powerful tool in asymmetric synthesis.…”
mentioning
confidence: 99%
“…However, when the phosphoric acid (S)-P6 and MgBu 2 were employed in the absence of cinchona alkaloids, almost no product was generated (entries 8, 10). On the contrary, by the use of quinine and MgBu 2 as combinational catalysts in the cross reaction led to the cyclization adduct with unsatisfactory diastereoselectivity and low ee values (entries 9,11). Moreover, it should be noted that the use of phosphoric acid (S)-P6' that was purified on silica gel and not washed with HCl led to a product with dramatically decreased enantioselectivity (entry 12).…”
mentioning
confidence: 99%